Dampak Penggunaan Teknologi Keuangan dan Literasi Keuangan Digital terhadap Kinerja Keuangan UMKM dengan Kompetensi Digital sebagai Variabel Moderasi - CHUSNUL MAULIDINA HIDAYAT; Alexandro Damar Tirta; Kurnia Indah Sumunar (Universitas Multi Data Palembang, 2026)
The development of digital technology encourages the use of Financial Technology (FinTech) as a strategy to improve the financial performance of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the effect of the use of Financial Technology and digital financial literacy on the financial performance of MSMEs with digital competence as a moderating variable. This study uses a quantitative approach with a survey method on MSMEs that have used FinTech services. Data were collected through a structured questionnaire using a Likert scale and analyzed using multiple linear regression analysis. The results show that the use of Financial Technology has a positive and significant influence on the financial performance of MSMEs. Conversely, digital financial literacy does not significantly influence the financial performance of MSMEs. Digital competence is not proven to moderate the influence of the use of Financial Technology or digital financial literacy on the financial performance of MSMEs, but has a positive and significant direct influence on the financial performance of MSMEs. This study emphasizes the importance of utilizing FinTech and strengthening practical digital competence in improving the financial performance of MSMEs in the digital economy era.